Discovering the Power of Spiritual Encounters to State of Social Wellbeing and Political Consciousness: A Phenomenological Study on Former Prisioner’s Experiences - Mohammad Irfan (Political Sciences Program Study, 2024)
This study discusses the importance of spiritual encounter to state of social wellbeing and political consciousness. This study took a cases from former prisoners who previously lived with many kinds of deviant behavior in their live. The deviance behavior was trigger by many aspects such as family, environment, poverty and so on. The enlightment they experienced have significant effect to social wellbeing and political conciousness. This study importance in the context of new perspective about politics and social welfare of individual or society. This research uses a phenomenological method. Data collection through observation and indeepth-interviews. The subjects in this research is former prisoners who had experienced a conversion from the dimension of spirituality. The subjects reside in Kuningan, West Java and Kulonprogo, Yogyakarta. The results of this study showed that there are three fundamental aspects that accompany the formation of conversion of spirituality experienced by former prisoners. The three aspects are inner conflict, inquiry, and commitment. After experiencing these conditions, there is state of mental stability to fully convert spiritually to religious values, which is marked by religiously observant behavior and completely abandoning criminal acts that have become a habit. What is then necessary from this conversion is its effect to their live in the form of state of wellbeing and political conciousness. The effects change their live at whole. This study concludes that spiritual encounter has a deep meaning not only to life state of wellbeing a person or society but also to political conciousness.